Clinical application of a modified predeposit autologous red blood cell apheresis in multistage spinal fusion: a single-center retrospective study - Xu, Xiao-Ping; Que, Wen-Jun; Yu, Ze-Bo; Shen, Jie-Liang; Hu, Zhen-Ming; Yang, Xiao-Liang; Hao, Jie (Frontiers in Medicine, 2023)
Purpose: To evaluate the efficacy and safety of predeposit autologous RBC apheresis (PARA) in the patients undergoing multilevel spinal fusion surgery. Methods: A total of 112 patients from January 2020 to June 2022 were divided into two groups according to PARA: the PARA group (n=51) and the control group (n=61). Basic characteristics of patients, outcomes, transfusion cost, hospitalization cost, length of stay, complications, changes of hemoglobin and hematocrit levels between the two groups were compared. Results: Baseline characteristics were similar in both groups. No significant differences were found in functional outcomes including VAS score (p=0.159), ODI score (p=0.214), JOA score (p=0.752) , SF-36 score (p=0.188) between the PARA and control groups. The amount and rate of intraoperative and perioperative allogeneic RBC transfusion were significantly higher in the control group than in the PARA group (p < 0.001). The postoperative (9.04±3.21 vs. 11.05±3.84, p=0.004) and total length of stay (15.78±3.79 vs. 17.36±4.08, p=0.038) in the PARA group were significantly less than that in the control group, respectively. Despite no difference in hospitalization cost (p=0.737), the total blood transfusion cost in the PARA group was significantly lower, compared with the control group (p < 0.001). For safety evaluation, there were no significant difference in Hb and Hct levels between the two groups at admission, on the postoperative day 1 and postoperative day 3, respectively (p＞0.05). Moreover, the number of postoperative infection in the PARA group was significantly lower than that in the control group (p=0.038). Conclusion: PARA was a novel, safe and high efficient technique for mass autologous blood preparation in a quite short preparation time. This method could significantly reduce the amount of allogeneic blood transfusion and length of stay, which could provide theoretical basis for following clinical practice about the technique.